Ingestion of plastic litter by the sandy anemone Bunodactis reynaudi. (December 2020) - Weideman, Eleanor A.; Munro, Christie; Perold, Vonica; Omardien, Aaniyah; Ryan, Peter G.
Abstract: Ingestion of anthropogenic litter has been well documented in marine vertebrates, but comparatively little is known about marine invertebrates. We report macrolitter ingestion by the sandy anemone Bunodactis reynaudi at Muizenberg beach in False Bay, South Africa. Monthly surveys from May 2015 to August 2019 collected 491 ingested litter items (9.4 ± 14.9 items·month -1, 39.8 ± 71.5 g·month -1 ), of which >99% were plastic. The number of ingested items was correlated with the abundance of stranded items and ingestion peaked in autumn when seasonal rains washed more litter into the bay. Most ingested litter was clear (39%), white (16%) and black/purple (15%). Comparison with environmental litter showed selection for flexible plastics, particularly bags/packets and food packaging. Experimental feeding trials found that B. reynaudi selected for pieces of HDPE bag suspended in seawater for 2–20 days, suggesting that biofilms enhance the palatability of flexible plastics. Studies are needed to assess the possible impacts of plastic ingestion on B. reynaudi . While only a small proportion of the population currently ingest litter, ingestion might become more common if environmental litter loads increase. This might negatively affect the anemone's ability to respond to other environmental changes such as increasing levels of heavy metal pollution. Graphical abstract: Image 1 Highlights: We report the first record of macroplastic ingestion by a sessile anemone. Approximately 1% of Bunodactis reynaudi ingested litter items each month. B. reynaudi preferred flexible plastics (bags/packets and food packaging). The incidence of ingestion was linked to litter abundance in the environment. Feeding trials suggest that biofilms enhance the palatability of HDPE bags.